The Montefeltro conspiracy a Renaissance mystery decoded - Simonetta, Marcello 1968- (Doubleday, 2008)
The Italian Renaissance is remembered as much for intrigue as it is for art, with papal politics and infighting among Italy's many city-states. The attempted assassination of the Medici brothers in Florence in 1478 is one of the best-known examples of the machinations of the age. While the assailants were the Medici's rivals, the Pazzi family, questions have always lingered about who really orchestrated the attack. Five centuries later, Marcello Simonetta, working in a private archive in Italy, stumbled upon a coded letter written by Federico da Montefeltro, the Duke of Urbino, to Pope Sixtus IV, containing proof of a power grab by the Pope for control of Florence. Montefeltro, long believed a close friend of Lorenzo de Medici, was in fact conspiring with the Pope to unseat the Medici. Their failure changed the course of Italian and papal history.--From publisher description.
Includes bibliographical references and index
Keywords: Medici, Lorenzo de' -- 1449-1492 -- Adversaries; Medici, Giuliano de' -- 1453-1478 -- Adversaries; Sixtus -- IV -- Pope -- 1414-1484 -- Political activity; Federico -- da Montefeltro, Duke of Urbino -- 1422-1482 -- Political activity; Botticelli, Sandro -- 1444 or 5-1510 -- Themes, motives; Simonetta, Ciccus -- ca. ca. 1410-1480; Pazzi -- Familie -- ca. 13.Jh.-15.Jh.; Botticelli, Sandro -- 1445-1510 -- Primavera; Medici -- Familie : 13.-18. Jahrhundert; Montefeltro, Federigo da -- 1422-1482; Geschichte 1400-1500; Geschichte 1476-1482; Geschichte; Pazzi Conspiracy, 1478; Cryptography; Politics in art; Verschwörung; Italien; Italy -- History -- 15th century; Italy -- History -- 15th century -- Sources; Florenz; Quelle